Simultaneous tracking of Pseudomonas aeruginosa motility in liquid and at the solid-liquid interface reveals differential roles for the flagellar stators - Hook, AL; Flewellen, JL; Dubern, J-F; Carabelli, AM; Zaid, IM; Berry, RM; Wildman, RD; Russell, N; Williams, P; Alexander, MR (American Society for Microbiology, 2019)
Bacteria sense chemicals, surfaces, and other cells and move toward some and away from others. Studying how single bacterial cells in a population move requires sophisticated tracking and imaging techniques. We have established quantitative methodology for label-free imaging and tracking of individual bacterial cells simultaneously within the bulk liquid and at solid-liquid interfaces by utilizing the imaging modes of digital holographic microscopy (DHM) in three dimensions (3D), differential interference contrast (DIC), and total internal reflectance microscopy (TIRM) in two dimensions (2D) combined with analysis protocols employing bespoke software. To exemplify and validate this methodology, we investigated the swimming behavior of a Pseudomonas aeruginosa wild-type strain and isogenic flagellar stator mutants (motAB and motCD) within the bulk liquid and at the surface at the single-cell and population levels. Multiple motile behaviors were observed that could be differentiated by speed and directionality. Both stator mutants swam slower and were unable to adjust to the near-surface environment as effectively as the wild type, highlighting differential roles for the stators in adapting to near-surface environments. A significant reduction in run speed was observed for the P. aeruginosa mot mutants, which decreased further on entering the near-surface environment. These results are consistent with the mot stators playing key roles in responding to the near-surface environment.